High-throughput screening of microbial strains in large-scale microfluidic droplets - Zhang, Zhidong; Guo, Qi; Wang, Yuetong; Huang, He (Frontiers in Bioengineering and Biotechnology, 2023)
The transformation of engineered microbial cells is one pivotal link in green biomanufacturing. Its representative application research involves genetic modification of microbial chassis to impart them targeted traits and functions able to more effectively synthesize the desired products. Microfluidics, as an emerging complementary solution, focuses on controlling and manipulating the fluid in the channels at the microscopic scale. One of its subcategories is droplet-based microfluidics (DMF), which could generate discrete droplets through immiscible multiphase fluids at kHz frequencies. Up to now, the droplet microfluidics has been successfully applied to a variety of microbes covering bacteria, yeast, and filamentous fungi, and realized the detection of massive metabolites of strain products, such as polypeptides, enzymes, and lipids. In summary, we firmly believe that droplet microfluidics has evolved into a powerful technology that will pave the way for high-throughput screening of engineered microbial strains in green biomanufacturing industry.